Photovoltaic properties of Cu2O-based heterojunction solar cells using n-type oxide semiconductor nano thin films prepared by low damage magnetron sputtering method. (March 2019) - Miyata, Toshihiro; Watanabe, Kyosuke; Tokunaga, Hiroki; Minami, Tadatsugu
Abstract: We improved the photovoltaic properties of Cu2 O-based heterojunction solar cells using n-type oxide semiconductor thin films prepared by a sputtering apparatus with our newly developed multi-chamber system. We also obtained the highest efficiency (3.21%) in an AZO/p-Cu2 O heterojunction solar cell prepared with optimized pre-sputtering conditions using our newly developed multi-chamber sputtering system. This value achieves the same or higher characteristics than AZO/Cu2 O solar cells with a similar structure prepared by the pulse laser deposition method.